Testing for causality between taxation and government spending: an application of Toda-Yamamoto approach - Abdul Aziz, Mariam; Habibullah, Muzafar Shah; Wan Ngah, Wan Azman Saini; Mohamed, Azali (Universiti Putra Malaysia Press, 2000)
The purpose of the present study is to investigate the causal relationship between the government tax revenues and government expenditures in Malaysia. We employ the Granger long run noncausality test as proposed by Toda and Yamamoto (1995) to test the causal relationships between government spending and tax revenues for the period 1960 to 1997. The evidence generally supports the existence of bi-directional casuality between government spending and tax revenues.